Above- and belowground biodiversity jointly tighten the P cycle in agricultural grasslands - Yvonne Oelmann (Nature Portfolio, 2021)
Relationships between biodiversity and phosphorus cycling and the underlying processes are complex. Here the authors analyse a biodiversity manipulation experiment and an agricultural management gradient to show how plant and mycorrhizal fungal diversity promote phosphorus exploitation.